Comparative assessment of thawing methods for frozen rooster sperm - Nizam, Mustafa Yigit; Selçuk, Murat; Kirikkulak, Murat (Frontiers in Veterinary Science, 2025)
IntroductionCryopreservation, widely used in commercial poultry breeding, often reduces sperm motility, viability, and DNA integrity due to cryopreservation-induced damage. This study evaluates the effects of water bath and dry thawing systems on the post-thaw quality of rooster spermatozoa, addressing these challenges and exploring methods to enhance sperm quality.MethodsThe study compared the performance of water bath and dry thawing systems, both operated at 37°C for 30 s. Post-thaw assessments included sperm motility, morphology, kinematic characteristics, and DNA integrity. Key parameters such as total motility, progressive motility, curvilinear velocity (VCL), average path velocity (VAP), straight-line velocity (VSL), viability, morphological abnormalities, and DNA damage metrics were analyzed.ResultsThe dry thawing system significantly improved sperm quality compared to the water bath method. Total motility and progressive motility were higher in the dry thawing system (82.38 and 33.18%, respectively) compared to the water bath method (68.14 and 21.20%). Kinematic parameters, including VCL (79.41 vs. 66.49 μm/s), VAP (47.52 vs. 37.42 μm/s), and VSL (27.18 vs. 21.59 μm/s), were superior in the dry thawing system. Viability improved (82.2 vs. 73.7%), while morphological abnormalities were reduced (23.9 vs. 35.8%). DNA integrity metrics, such as Tail DNA (%; 77.37 vs. 81.11%) and Olive Tail Moment (15.28 vs. 16.93), also showed reduced damage.DiscussionThe dry thawing system offers significant operational advantages, including portability, contamination-free operation, and consistent temperature maintenance, making it ideal for on-site applications. These features, combined with its ability to enhance sperm quality, highlight the dry thawing system as an effective alternative for poultry breeding. Its adoption could improve artificial insemination outcomes and address challenges associated with cryopreservation-induced damage during thawing.